Analysis of Career Development and Engagement on Gen Z Retention via Commitment in Jakarta Tech Companies - Muhammad Rafi Dhia (Yayasan Insan Mulia Bima, 2024)
This study aims to examine the impact of Career Development and Employee Engagement on the retention of Generation Z employees in technology companies in Jakarta, with Organizational Commitment serving as a mediating variable. The research uses Career Development and Employee Engagement as independent variables and Employee Retention as the dependent variable. Data was gathered by distributing questionnaires to 140 employees working in technology companies in Jakarta. An associative quantitative approach was employed, utilizing primary data and applying Structural Equation Modeling (SEM) through Smart PLS. The findings reveal that Career Development significantly influences Employee Retention with a coefficient value of 0.497. Similarly, Employee Engagement has a positive and significant effect on Employee Retention, with a coefficient value of 0.224. Additionally, Career Development positively and significantly impacts Organizational Commitment with a coefficient value of 0.575, while Employee Engagement also positively and significantly affects Organizational Commitment with a coefficient value of 0.257. Furthermore, both Career Development and Employee Engagement positively and significantly influence Employee Retention through Organizational Commitment, with coefficient values of 0.160 and 0.072, respectively. Finally, Organizational Commitment has a significant effect on Employee Retention, with a coefficient value of 0.279.